The effectiveness of fading in programming a simultaneous form discrimination for retarded children - Sidman, Murray (1967)
A non-verbal teaching program, combined with reinforcement and extinction (Program Group), was compared with reinforcement and extinction alone (Test Group) in teaching retarded children to discriminate circles from ellipses. In the Program Group, fading techniques were used to transfer stimulus control from “bright vs. dark” to “form vs. no-form” and then to “circle vs. ellipse”. The Test Group had the task of learning the circle-ellipse discrimination with no prior teaching program. With the program, seven of 10 children learned the circle-ellipse discrimination. Without the program, one of nine learned. The eight Test-Group children who failed to learn circle vs. ellipse were then given the opportunity to learn the form no-form discrimination by reinforcement and extinction alone, without fading. Six of the eight learned, but only three of these six then learned circle vs. ellipse on a second test. All seven Program-Group children who had learned form vs. no-form also learned the circle-ellipse discrimination by means of fading; each of the seven made fewer errors than any of the three who succeeded on the second test. Children who failed to learn circle vs. ellipse adopted response patterns incompatible with the development of appropriate stimulus control.